Exploring secondary writing teachers’ metacognition: an avenue to professional development - Martin, Joy Alison (Kansas State University, 2013)
Writing teachers teach students to read, write, and think through text. They draw upon their own comprehension to determine if, when, and how to intervene in directing students to deeper, more thoughtfully written texts by encouraging them to monitor and regulate their thoughts—to be metacognitive. Writing itself has been called “applied metacognition,” for it is essentially the production of thought (Hacker, Keener, & Kircher, 2009, p. 154). Yet little is known about the metacognitive practices and behaviors of those who teach writing. The purpose of this instrumental, collective case study was to explore and describe writing teachers’ metacognition as they took part in two range-finding events in a midwestern school district. Participants were tasked with reading and scoring student essays and providing narrative feedback to fuel training efforts for future scorers of the district’s writing assessments. Each range-finding event constituted a case with fourteen participants. Three administrative facilitators and four retired English teachers participated in both events, along with seven different practicing teachers per case. The study concluded that, indeed, participants perceived and regulated their thinking in numerous ways while reading and responding to student essays. With Flavell’s (1979) theoretical model of metacognition as a framework for data analysis, 28 distinct content codes emerged in the data: 1) twelve codes under metacognitive knowledge of person, task, and strategy, 2) seven codes under metacognitive experiences, 3) six codes under metacognitive goals (tasks), and 4) three codes under metacognitive actions (strategies). In addition, three dichotomous themes emerged across the cases indicating transformational distinctions in teachers’ thinking: 1) teaching writing and scoring writing, 2) confusion and clarity, and 3) frustrations and fruits. The study highlighted the potential of improving teachers’ meta-thinking about teaching and assessing writing through dialectic conversations with other professionals. Its findings and conclusions implicate teacher educators, practicing teachers, and school district administrators to seek opportunities for cultivating teachers’ awareness, monitoring, and regulation of their thoughts about content, instruction, and selves to better serve their students.
Keywords: Metacognition; Reading comprehension; Writing instruction; Writing assessment; Professional development; Language Arts (0279)